Registro e dinâmica populacional de Raoiella indica HIST (Acari: Tenuipalpidae) em Cocos nucifera LIinnaeus (Arecales: Arecaceae) no Maranhão - Santos, Taynara Cruz dos (2021)
Raoiella indica Hirst (Acari: Tenuipalpidae) is an invasive phytophagous mite with a wide range of host plants. In recent years, R. indica has expanded its geographic distribution in the Americas. In areas recently invaded by R. indica, it is essential to carry out the occurrence record as well as long-term population ecology studies. In this context, the present study aimed to record the occurrence of the red palm mite R. indica in Maranhão, and to study the population dynamics and the relative contribution of abiotic and biotic factors to the population density of this pest. Raoiella indica was recorded for the first time in coconut plantations (Cocos nucifera L.) in 2018, in the Iguaíba community, rural area of the municipality of Paço do Lumiar, Maranhão. Then, the structure and population dynamics of R. indica was evaluated during the beginning of the dry (2019-2020: August, September and October) and rainy (2020-2021: January, February and March) seasons in five commercial coconut crops of the green dwarf variety, for two years. Seasonal changes were observed in the structure and population dynamics of R. indica. The egg stage showed higher density per cm2 of leaf area compared to immature and adults of R. indica at the end of the sampling period. The density of eggs and immatures of R. indica was not affected by seasonality. However, the number of adults of R. indica varied seasonally, with higher population densities recorded in the rainy season compared to the dry season. Abiotic variables explained different fractions of the variance for each stage of R. indica development. The results demonstrate that it is important to consider the population structure in studies of population dynamics of R. indica, since each stage of development responds uniquely to the local environment over time. A higher density of R. indica was observed compared to the population density of predatory mites of the family Phytoseiidae during the months of sampling. Most of the variance for the population density of R. indica was explained by the density of Phytoseiidae. Additionally, the density of R. indica was positively correlated with the density of predatory mites of the Phytoseiidae family, confirming the result of the hierarchical partition analysis. In conclusion, the biological control exerted by predatory mites of the Phytoseiidae family was the main mechanism regulating the population density of R. indica in commercial cultivations of green dwarf coconut variety